On the Closed Forms of Z(pq), q = kp ± 10 (The Chittagong University Journal of Science, 2021)
This paper derives the closed form expressions of Z(pq), where p and q ( > p) are primes, and q is of the forms q = kp ± 10 for some (positive) integer k, and Z(.) is the pseudo Smarandache function.The Chittagong Univ. J. Sci. 40(1) : 96-105, 2019